Learning styles of students and teaching strategies of instructors in pharmacy schools in Metro Manila - Belontidos, Dianne Camille B.
Learning styles and teaching strategies are two important factors to consider in the classroom in order to create a proper learning environment. In this study, the learning styles and the perceived teaching strategies of students from their instructors were determined through distribution of questionnaires to 394 students in pharmacy schools under PACOP in Metro Manila. Similarly, survey questionnaires were administered to 44 instructors (49.44%) to determine their teaching strategies. The tools used were Felder-Silverman Index of Learning Styles ® and Felder-Solomon Model of Teaching Style®. No significant differences were found when learning styles and teaching strategies were related to demographic factors, through Chi-square Test/Fisher's Exact Test. The most common learning styles of pharmacy students are : active, sensory, visual, and sequential. The most perceived teaching strategies by students from their instructors are: passive, concrete, verbal and sequential. The most common teaching strategies according to instructors are: active, concrete, verbal, and global. To test the relationships among the three, Fisher's McNemar Test was used. Results showed that there are existing mismatches or imbalances among the three. Mismatches were evident between the student's learning styles with instructors' teaching strategies, the student's learning styles with student perceived teaching strategies, and the student perceived teaching strategies with instructors' teaching strategies as determined by the tool. These information may be used to determine in what particular areas of learning and teaching the strategies may be focused.